Online experimentation and sampling in cognitive aging research - Greene, Nathaniel R; Naveh-Benjamin, Moshe (Psychology and aging, 2022)
Online data collection methods have become increasingly popular in many domains of psychology, but their use in cognitive aging studies remains relatively limited. Is it time for cognitive aging researchers to embrace these methods? Here, we weigh potential advantages and disadvantages of conducting online studies with young and older adults, relative to lab-based studies, with a particular focus on the study of human memory and aging. With online studies, it may be possible to assess whether age-related effects on cognition obtained in the laboratory generalize to other situations with different environmental or subject characteristics. However, there are many open questions about the representativeness of older adults on online data collection platforms, and issues surrounding data quality, selection effects, and other biasing characteristics, which must be carefully handled in cognitive aging studies which recruit young and older adult participants online. We consider the benefit of conducting experimentation both in the lab and online in providing converging evidence on a research question, and we offer an example of an experiment on adult age differences in associative recognition that was conducted in the laboratory and online. We also provide practical recommendations for ways to maximize the potential for online studies to contribute to our understanding of cognitive aging. (PsycInfo Database Record (c) 2022 APA, all rights reserved).